Relationship between gestational diabetes and endometrial cancer - Zohreh Yeganeh; Zohre Sheikhan; Nourossadat Kariman; Parasto Hajian; Malihe Nasiri (Mashhad University of Medical Sciences, 2019)
Introduction: Endometrial cancer is the most common gynecological malignancy in women worldwide. The rate of endometrial cancer is increasing in Iran. Various factors affect the incidence of endometrial cancer. The role of gestational diabetes in these factors is unclear. Therefore, this study was performed with aim to compare the history of gestational diabetes in women with endometrial cancer and healthy women. Methods: This retrospective analytical study was performed on 360 women referring to hospitals of Shahid Beheshti University of Medical Sciences in Tehran in 2017. Data was collected by interview and completing the questionnaire of demographic, fertility characteristics, medical records and endometrial cancer information. Data were analyzed by SPSS software (version 21) and Chi-square, independent t-test, Odds ratio and Logistic Regression. P<0.05 was considered statistically significant. Results: In this study, 29 women (8%) had history of gestational diabetes that 17 women (14.2%) were in case group and 12 (5%) in control group. There was significant difference between two groups of women with endometrial cancer and healthy women in terms of gestational diabetes (p<0.05). Conclusion: History of gestational diabetes increases the risk of endometrial cancer; therefore it can be used for primary prevention and early diagnosis of endometrial cancer.